The Effect of Entrepreneurial Behavior on Salted Fish Business Performance at Muara Angke - Nurfiqayumi Arnis; Lukman M. Baga; Burhanuddin Burhanuddin (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
Business performance was one of the benchmarks of entrepreneurial behavior so the concept of entrepreneurial behavior in businessmen is important, because it will impact on business performance. Entrepreneurial behavior is formed by two factors namely individual and environmental factors. The objective of this research were to analyze the effect of individual and environmental factors that influence entrepreneurial behavior and to analyze the influence of entrepreneurial behavior on business performance of Salted fish in Muara Angke. This research used Structural Equation Modeling-Partial Least Square (SEM-PLS) 3.0 for quantitative analysis. The result of this research indicated that individual factor had a positive effect and it was significant on entrepreneurial behavior with coefficient value 0.317 and t-statistics 3.860, while the environmental factor in salted fish business had a positive effect, and it was insignificant on entrepreneurial behavior because the value of t-statistics was 1,262 < 1.96. Entrepreneurial behavior had a positive effect and it was significant on business performance. This can be seen from the t-statistic value of 2.551 > 1.96, which means that any increase of entrepreneurial behavior will improve business performance of salted fish businessmen in Muara Angke.Keywords: entrepreneurial behavior, business performance, salted fish, partial least square